Dynamics of Soil CO2 Efflux and Vertical CO2 Production in a European Beech and a Scots Pine Forest - Jochheim, Hubert; Wirth, Stephan; Gartiser, Valentin; Paulus, Sinikka; Haas, Christoph; Gerke, Horst H.; Maier, Martin (Frontiers in Forests and Global Change, 2022)
The conversion of coniferous forest to deciduous forest is accompanied by changes in the vertical distribution of fine roots and soil organic carbon (SOC) content. It is unclear how these changes affect soil CO2 efflux and vertical soil CO2 production, considering changing climate. Here, we present the results of a 6-year study on CO2 efflux, covering relatively warm-dry and cool-wet years. A combination of the flux-gradient method and closed chamber measurements was used to study the CO2 efflux and the vertical distribution of soil CO2 production in a beech (Fagus sylvatica L.) and a pine (Pinus sylvestris L.) forest in northeast Germany. We observed, on average, similar CO2 efflux with 517 (±126) and 559 (±78) g C m–2 a–1 for the beech site and the pine site, respectively. CO2 efflux at the beech site exceeded that at the pine site during the wet year 2017, whereas in dry years, the opposite was the case. Water availability as indicated by precipitation was the primary determining long-term factor of CO2 efflux, whereas seasonal variation was mainly affected by soil temperature, and—in the case of beech—additionally by soil water content. CO2 efflux decreased more dramatically (-43%) at the beech site than at the pine site (-22%) during the warm-dry year 2018 compared to the cool-wet year 2017. We assumed that drought reduces heterotrophic respiration (Rh) at both sites, but additionally decreases autotrophic respiration (Ra) at the beech stand. Soil CO2 production at the beech site ranged over a greater soil depth than at the pine site, attributed to different fine root distribution. The organic layer and the A horizon contributed 47 and 68% of total CO2 efflux at the beech site and the pine site, respectively. The seasonal patterns of different CO2 efflux between both sites were assumed to relate to different phases of tree physiological activity of deciduous compared to evergreen tree species.